2017
DOI: 10.7205/milmed-d-16-00405
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Lifestyle Changes: Impact on Weight, Quality of Life, and Psychiatric Symptoms in Veterans With Mental Illness

Abstract: Counseling Veterans to practice TLCs provides a holistic adjunct to current treatments for mental illness. TLCs may confer multiple benefits upon Veterans with mental illness, enhancing quality of life and well-being along with weight management efforts. As these were pilot studies, the samples sizes were relatively small and a control group was lacking. Our findings may have broader implications supporting a holistic approach in both primary and mental health care settings. Future research will expand this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…26,108 Seven studies (9%) used other, more unique measures to assess physical function, including timed and distance walking tests 27,30,33,74,86,109 and balance scales. 23 In terms of reported findings, 57 studies (73%) [17][18][19]21,22,24,26,27,[32][33][34][35][36][37][38][39][40]62,63,[65][66][67][68][69][70][71]73,74,76,80,82,83,[85][86][87][88][89][90][91][92][94][95]…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,108 Seven studies (9%) used other, more unique measures to assess physical function, including timed and distance walking tests 27,30,33,74,86,109 and balance scales. 23 In terms of reported findings, 57 studies (73%) [17][18][19]21,22,24,26,27,[32][33][34][35][36][37][38][39][40]62,63,[65][66][67][68][69][70][71]73,74,76,80,82,83,[85][86][87][88][89][90][91][92][94][95]…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
“…86 Other outcome measures included changes in anthropometrics, cardiovascular and diabetes risk reduction, and behavior change. Anthropometric outcomes included changes in body weight, 17,22,31,32,67,73,85,[88][89][90]93,95,99,100,112 decreases in waist circumference, 19,32,75,76,95,100 and reductions in body mass index. 19,26,32,103,112 Results related to cardiovascular risk factors included changes in blood lipid levels 75,100 and improved blood pressure.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
“…In overweight and obese veterans, low fruit and vegetable consumption is often associated with tobacco use [130]. Unhealthy dietary and lifestyle habits, including smoke, are common in veterans [131][132][133], increasing the risk of cancer and cardiovascular diseases (CVD) [134].…”
Section: Healthy Diet For Veteransmentioning
confidence: 99%
“…Mental illness is also related with poor nutrition [132,133] and both PTSD and depression are associated with binge eating disorders in veterans [135]. Data from meta-analysis indicated that subjects with PTSD had a high risk of developing impaired memory [136], Type 2 diabetes mellitus [137], CVD [138] and metabolic syndrome [139].…”
Section: Healthy Diet For Veteransmentioning
confidence: 99%
See 1 more Smart Citation